Cognitive behavioural therapy in improving adherence for diabetes management. - Abdul Khaiyom, Jamilah Hanum (2017)
The presentation addressed how cognitive behavioural therapy (i.e., a form of psychotherapy) may help in improving treatment adherence for diabetes. The five elements in cognitive behavioural therapy (i.e., events/situations, thoughts, feelings, physiological reactions, and actions) were discussed and linked to the concept of diabetes management. The possibility of adherence or resistance towards treatment were discussed.